Bioseparation of papain from Carica papaya latex by precipitation of papain- poly (vinyl sulfonate) complexes - Braia, Mauricio Javier (2013)
The formation of insoluble complexes between enzymes and polyelectrolytes is a suitable technique for isolating these biomolecules from natural sources, because it is a simple and rapid technique that allows the concentration of the protein. This technique can be used in most purification protocols at the beginning of the downstream process. The aim of this investigation is to isolate papain from Carica papaya latex by precipitation of insoluble complexes between this enzyme and poly (vinyl sulfonate). The papain-poly (vinyl sulfonate) complex was insoluble at pH lower than 6, with a PVS/PAP stoichiometric ratio of 1:279. Ionic strength affected the complex formation. The presence of the polymer increased the enzymatic activity and protected the enzyme from autodegradation. The optimal conditions for the formation of insoluble papain-polyelectrolyte complex formation were applied to C. papaya latex and a high recovery was obtained (around 86%) and a purification factor around 2. This method can be applied as an isolation method of papain from C. papaya latex or as a first step in a larger purification strategy.